1999
DOI: 10.1190/1.1444629
|View full text |Cite
|
Sign up to set email alerts
|

Image mispositioning due to dipping TI media: A physical seismic modeling study

Abstract: A scaled physical model was constructed to investigate the magnitudes of imaging errors incurred by the use of isotropic processing code when there is seismic velocity anisotropy present in the dipping overburden. The model consists of a block of transversely isotropic (TI) phenolic material with the TI axis of symmetry dipping at an angle of 45°. Its scaled thickness is 1500 m, and it is intended to simulate the dipping clastic sequences found in many fold-thrust belts. A piece of isotropic Plexiglas, affixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…The shot gather shows that the reflection NMO of the P-waves reflected from a horizontal anisotropic layer with θ = 45° is hyperbolic within the largest offset/depth = 1.4 (Isaac and Lawton 1999). In our study, the ratio of the largest offset/depth for the models where θ = 0°, 30°, 45°, 60° and 90° is respectively 1.75, 1.75, 1.38, 1.25, and 1.63.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The shot gather shows that the reflection NMO of the P-waves reflected from a horizontal anisotropic layer with θ = 45° is hyperbolic within the largest offset/depth = 1.4 (Isaac and Lawton 1999). In our study, the ratio of the largest offset/depth for the models where θ = 0°, 30°, 45°, 60° and 90° is respectively 1.75, 1.75, 1.38, 1.25, and 1.63.…”
Section: Discussionmentioning
confidence: 93%
“…Our results suggest that the measurable nonhyperbolic reflection NMO can only be detected in highly anisotropic media and at the far offset. Uren et al (1991), and Isaac and Lawton (1999) showed that the near offset trace has a greater deviation of the reflection position from the CMP than does the far offset trace. In the present study, this is only the case for the models where θ = 45°, and 60°.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that isotropic algorithms applied to modeling and imaging in transversely isotropic (TI) media produce mispositioning of structures (Martin et al, 1992;Larner and Cohen, 1993;Isaac and Lawton, 1999). In response to these shortcomings many imaging methods for TI media have been developed (Meadows et al, 1987;Uren et al, 1990;Gonzalez et al, 1991;Kitchenside, 1991;Sena and Toksoz, 1993;Meadows and Abriel, 1994;Uzcategui, 1995;Le Rousseau, 1997;Le Rousseau and de Hoop, 2001;Ferguson and Margrave, 2002).…”
Section: One-way Dual-domain Propagator For Scalar Qp-wave In Vti Mediamentioning
confidence: 99%
“…Using the VTI assumption to image structures characterized by TTI anisotropy introduces both kinematic and dynamical errors in migrated images. For example, Vestrum et al (1999) and Isaac and Lawyer (1999) show that seismic structures can be mispositioned if isotropy, or even VTI anisotropy, is assumed when the medium above the imaging targets is TTI. To carry out elastic wave-equation migration for TTI models and apply the imaging condition that crosscorrelates the separated wave-modes, the wave-mode separation algorithm needs to be adapted to TTI media.…”
Section: Introductionmentioning
confidence: 99%